In vivo multi spectral colonoscopy in mice - Hohmann, Martin; Ganzleben, Ingo; Grünberg, Alexander; Menezes, Jean Gonzales; Klämpfl, Florian; Lengenfelder, Benjamin; Liebing, Eva; Heichler, Christina; Neufert, Clemens; Becker, Christoph; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2022)
Multi- and hyperspectral endoscopy are possibilities to improve the endoscopic detection of neoplastic lesions in the colon and rectum during colonoscopy. However, most studies in this context are performed on histological samples/biopsies or ex vivo. This leads to the question if previous results can be transferred to an in vivo setting. Therefore, the current study evaluated the usefulness of multispectral endoscopy in identifying neoplastic lesions in the colon. The data set consists of 25 mice with colonic neoplastic lesions and the data analysis is performed by machine learning. Another question addressed was whether adding additional spatial features based on Gauss-Laguerre polynomials leads to an improved detection rate. As a result, detection of neoplastic lesions was achieved with an MCC of 0.47. Therefore, the classification accuracy of multispectral colonoscopy is comparable with hyperspectral colonoscopy in the same spectral range when additional spatial features are used. Moreover, this paper strongly supports the current path towards the application of multi/hyperspectral endoscopy in clinical settings and shows that the challenges from transferring results from ex vivo to in vivo endoscopy can be solved.
CRIS-Team WoS Importer:2022-06-10